Associations between competitive anxiety, athlete characteristics and sport context: evidence from a systematic review and meta-analysis - Rocha, Viviane Vedovato Silva (2018)
Background: There is a vast literature investigating the possible associations between competitive anxiety, athlete variables and sports context. As far as we are concerned, there is no study which has compiled such findings to produce more robust evidence on this topic. Objectives: The aim of the study was to conduct an exploratory systematic review of the literature followed by a meta-analysis in order to investigate possible associations between competitive anxiety, socialdemographic characteristics, profile of the athlete and sports context. Methods: Systematic searches of PubMed, PsycInfo, Web of Science, Lilacs and SciELO electronic databases were performed to identify studies published between January 2006 and January 2018, including a manual search in the references of the selected studies. Results: A total of 59 studies were included for qualitative synthesis and 27 for meta-analysis. More robust associations were observed between competitive anxiety and female gender, lower age, and less experience time. Discussion: Knowing the variables which exert influence on competitive anxiety can be relevant to plan specific treatment and intervention programs, enabling the athlete´s development beyond technical and physical preparation.